The creation of new administrative units in Costa Rica: Monteverde and Puerto Jiménez cases - Aguirre Raftacco, Eugenia C. (2025)
For nearly four decades, Costa Rica’s territorial division remained unchanged at the cantonal level. This period of stability ended with the creation of the canton of Río Cuarto in 2017, followed by Monteverde and Puerto Jiménez between 2021 and 2022. This article analyzes the political factors that enabled the formation of these two cantons, highlighting the role of local leadership and their agency capacity. Using a qualitative methodology based on case studies, the article reconstructs the institutional trajectories and mobilization dynamics that made the territorial reform possible. The analysis draws on documentary sources and semi-structured interviews with relevant actors. The findings suggest that the creation of new cantons relied on a combination of strong community organization, narratives of state neglect, political articulation strategies, and peer learning processes, all of which allowed local leaderships to navigate the legislative path. The study contributes to the debate on territorial governance in decentralized contexts by showing that the proliferation of new cantons in Costa Rica responds not only to persistent institutional deficits, but also to emerging forms of local collective action that exceed traditional analytical frameworks through which this phenomenon has been previously addressed.